Application of a Continuously Active Antimicrobial Surface Coating in Two Professional Sports Training Facilities. (October 2020) - Grossman, Gavriel; Beck, Valerie; Watson, Dan; Toklu, Ece; El-Sayed, Maha
Abstract : Background: The role of surface contamination in infections is of interest in healthcare as well as other industries, especially where infections incur high cost. One such industry is professional sports, where infections pose significant risks to players and the organizations that employ them. Sports training facilities experience highly variable occupancy rates due to differing seasonal activities, presenting a measurement challenge because the relationship between occupancy and surface contamination is not well described. In a recent publication, a continuously active antimicrobial (CAA) surface coating demonstrated a reduction in bacterial bioburden in ICUs alongside a reduction in healthcare-associated infections (HAIs). Objective: We investigated the impact of a CAA surface coating on bioburden in 2 professional sports training facilities, despite changes in occupancy. Methods: A CAA surface coating was applied using an electrostatic sprayer to all surfaces in both facilities during a period of high-occupancy at facility A and during low occupancy at facility B. Surface cultures were taken using 3M Sponge-Sticks from lockers, gym equipment, and physiotherapy surfaces before treatment, 4–13 weeks after treatment at facility A and 4–23 weeks after treatment at facility B. Total aerobic bacteria counts were obtained by plating on tryptic soy agar, and geometric means of aerobic plate counts (APCs) were used to compare bioburden before and after treatment at both facilities and for an out-of-efficacy period at facility B (17–23 weeks). Occupancy rates were monitored as person days per week (pd/w) over the course of the study. Results: APC counts at facility A decreased 61% (585 CFU/100 cm 2 to 226 CFU/100 cm 2 ) from baseline to posttreatment, and occupancy remained constant (165 pd/w to 171 pd/w). At facility B, there was no significant change in APC (76 CFU/100 cm 2 to 80 CFU/100 cm 2 ), although occupancy increased >13, 000% during the treatment period (3 pd/w to 386 pd/w). During the out-of-efficacy period at facility B, total bacteria increased 170% (217 CFU/100 cm 2 ) compared to the treatment period, and the occupancy remained relatively constant (344 pd/w). Conclusions: Levels of bioburden were significantly influenced by the application of the CAA surface coating, especially considering the variation in occupancy in both facilities before, during, and after the efficacy period. Facility A saw a significant reduction in bioburden during the treatment period ( P < .0001), and a significant increase was observed at facility B during the out-of-efficacy period ( P < .0001) despite constant occupancy rates, demonstrating the ability of the surface coating to reduce bioburden levels despite large changes in occupancy. Funding: Allied BioScience, Inc, provided Funding: for this study. Disclosures: Gavri Grossman, Valerie Beck, and Daniel S Watson report salary from Allied BioScience.